Induction of Divergent Cell Death Pathways by Urea and Carbohydrazide Derivatives - (:unkn) unknown (My University, 2021)
BACKGROUND: The complexity of cancer biology and the development of chemotherapy resistance are two main obstacles to cancer treatment and necessitate novel anticancer molecules that target different cell death pathways. Modulation of endoplasmic reticulum (ER) stress and subsequent activation of the unfolded protein response (UPR) has been proposed as potential chemotherapeutic target, as prolonged ER stress can lead to cell death via apoptosis or necrosis. OBJECTIVE: The present study aims to evaluate the molecular mechanism underlying the cytotoxic activity of selected urea and carbohydrazide derivatives. METHODS: Cell proliferation assays were performed on HeLa, Capan1, MCF7, HCC1937, and MRC5 cell lines by WST-1 assay. The expression levels of selected ER stress, autophagy, and apoptosis marker proteins were compared by immunoblotting to characterize the underlying mechanism of cytotoxicity. Flow cytometry was used to detect apoptosis. RESULTS: Of the tested cytotoxic compounds, 3a, 4a, 5a, 6a, and 1b dramatically and 5b moderately increased ER stress-related CHOP protein levels. Interestingly, 5b but not 3a, 4a, 5a, 6a, or 1b increased the expression of pro-apoptotic proteins such as cleaved PARP-1 and cleaved caspase-3 and -7. Flow-cytometry analysis further confirmed that the cytotoxic activity of 5b but not the other compounds is mediated by apoptosis, which is also demonstrated by a significant increase in the percentage of late apoptotic cells (7-AAD/annexin V double-positive cells). CONCLUSION: Our results suggest that changing a substituent from trifluoromethyl to nitro in urea and carbohydrazide core structure alters the cell death mechanism from apoptosis to an apoptosis-independent cell death pathway. This study shows an example of how such simple modifications of a core chemical structure could cause the induction of divergent cell death pathways.
Keywords: apoptosis; urea; carbohydrazide derivatives; cell death; CHOP; necrosis; UPR